THE NEW PARADIGM FOR JUDGES IN DECIDING CRIMINAL CASES: BALANCING LEGAL CERTAINTY AND SUBSTANTIVE JUSTICE - Suviana Suwoto Mulyosudarmo; Vieta Imelda Cornelis; Siti Marwiyah; Wahyu Prawesthi (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The enactment of Law No. 1 of 2023 on the Criminal Code (KUHP) marks a fundamental transformation in Indonesia’s criminal justice system, shifting the paradigm from retributive justice toward corrective, rehabilitative, and restorative justice. This research aims to analyze the transformation of the judge’s role from being a mere “mouthpiece of the law” (la bouche de la loi) to becoming a progressive legal finder (rechtsvinding), while examining the balancing mechanism between formal legal certainty and substantive justice. Using a normative legal research method with conceptual and statutory approaches, this study finds that the new Criminal Code grants broad humanistic discretionary power to judges. This is reflected in Article 12 regarding the recognition of living law, Article 51 concerning holistic sentencing guidelines, and Article 54 regarding judicial pardon. The research findings emphasize that this new role requires judges to perform individualized sentencing that considers the subjective condition of the perpetrator and the restoration of the victim. However, the flexibility of this discretion brings consequences regarding the urgency of moral integrity and the accountability of legal reasoning (ratio decidendi). Without solid ethical standards, discretion risks falling into judicial arbitrariness. This research concludes that the success of national criminal law reform depends heavily on the intellectual readiness of judges to harmonize statutory texts with the sense of justice embedded within society.